Chemical literacy of teaching candidates studying the ıntegrated food chemistry ethnosciences course - Sumarnı, Woro; Sudarmin; Wiyanto; Rusılowatı, Ani; Susılanıngsıh, Endang (Journal of Turkish Science Education, 2017)
This research aimed to describe the chemical literacy of teaching candidates studying the integrated food chemistry ethnosciences course. The research sample comprised teaching candidates studying chemistry in a teachers’ education program in Central Java, Indonesia. In this descriptive research method, data was collected by using a chemical literacy test in narrative form regarding material integrated ethnosciences carbohydrates that have been declared valid by experts with a reliability of 0.81. The results revealed that the content aspects of students’ average chemical literacy achievement amounted to 31.8% included in the low category. Similarly, for science literacy achievement scores in the process domain, the indicators identifying scientific questions of 3.20 evaluate and design a scientific investigation of 2.26 and identify the scientific evidence of 2.95 from a maximum score of 5.0. These students’ chemical literacy achievement is also in accordance with the results of the analysis of student explanations on selected chemical concepts that are seen mostly in the category of partially correct answers. Therefore, it is necessary to improve the quality of learning that explicitly integrates aspects necessary to improve students’ chemical literacy.